Transformation of MSMEs in Putrapinggan Village Through Digital Marketing Training for Technology-Based Development - Dedeh Sri Sudaryanti; Andri Helmi Munawar; Ageng Asmara Sani; Allicia Deana Santosa (Yayasan Putra Adi Dharma, 2023)
The development of micro, small, and medium enterprises (MSMEs) play a crucial role in a country's economy. However, many MSMEs still face challenges in leveraging digital technology and online marketing to expand their businesses. This research aims to implement digital marketing training as an effort to enhance the technological capabilities of technology based MSMEs in Putrapinggan Village, Pangandaran Regency. The training method involves providing fundamental knowledge on digital marketing, online marketing strategies, social media management, and digital performance analysis.